Dimethyl sulfoxide modulates NF-kappa B and cytokine activation in lipopolysaccharide-treated murine macrophages. - Kelly, K A (1994)
Antioxidants are protective against septic shock in animal models. Recently, free radical scavengers have been found to inhibit the activation of the NF-kappa B protein in a number of cell lines. This transcriptional regulatory protein binds to the promoters of the proinflammatory cytokines tumor necrosis factor, interleukin-6, and the macrophage inflammatory proteins. The current work examined lipopolysaccharide-induced NF-kappa B activation in the J774 macrophage-like cell line and primary peritoneal macrophages from lipopolysaccharide-responsive (C3HeB/Fej) and -nonresponsive (C3H/HeJ) murine strains. The DNA-binding activity of the NF-kappa B protein directly correlated with mRNA expression for the genes encoding the proinflammatory cytokines and the free radical scavenging enzyme, superoxide dismutase. Both the p50 and p65 NF-kappa B subunits were detected on gel supershift assays. Minimal NF-kappa B activity was observed following exposure of C3H/HeJ macrophages to lipopolysaccharide. The antioxidant dimethyl sulfoxide decreased the level of NF-kappa B activation in the J774 cells. This correlated with decreased expression of cytokine mRNAs and tumor necrosis factor bioactivity. These results suggest that modulation of NF-kappa B activation may provide a mechanism through which antioxidants protect against endotoxemia in murine models.